Aspekty medyczno-prawne dotyczące żywienia w kontekście bezpieczeństwa ekologicznego żywności - Świerżewska, Julia; Kaszczewska, Salomea; Młodziejewski, Wojtek (Transfer of innovative technologies, 2021)
They know better all the features and risks of their business, and therefore they must be responsible for their safety. Implementation of the main elements of the new food safety control system in Ukraine takes place through the implementation of a permanent procedure based on the HACCP principles [1−3]. Now, entrepreneurs must identify potential hazards and risks of the production process and capacities, as well as take all necessary measures to minimize them. Together with greater responsibility the entrepreneurs receive more freedom. For example, the state cannot require the factory to have light walls above 1.8m. The quality is a subjective and personal concept, and safety requirements must prevent the harmful effects of products on the health of the consumer. At the same time, Ukrainians need to know what they are consuming. Therefore, lawmakers are currently working on a draft law on providing information to consumers about food. The new system to which Ukraine passes allows a clear distinction to be drawn between liabilities for causing harm due to the consumption of a dangerous product. According to the concept of the food chain «from the lawn to the table», the quality of the product must be baked at each stage of the commodity circulation, and each businessman is responsible for the safety of the food within its activities: the manufacturer − within the limits of production, the carrier − within the scope of transportation, the store − within storage and sale. Consequently, at each point of the food chain, the entrepreneur knows where the raw material or product came from and where it comes next. If the customer receives a health hazard product, this system helps to identify: who is responsible for causing harm. In this chain, there should be feed for productive animals. The draft law «On Safety and Hygiene of Forms» has already been developed and registered. If the feed contains harmful substances, they will continue to enter our body through products made from animal meat.